GLACIAL-INTERGLACIAL TERRIGENOUS PROVENANCE IN THE SOUTHEASTERN ATLANTIC OCEAN: THE IMPORTANCE OF DEEP-WATER SOURCES AND SURFACE CURRENTS - Latimer J.C.; Hendy I.L.; Gleason J.D.; Blum J.D.; Filippelli G.M. (My University, 2006)
Identifying terrigenous sources in deep-sea sediments may reveal temporal trends in paleocirculation and the relative role of eolian, upwelled, and hemipelagic Fe sources to surface waters. Bulk elemental and isotopic geochemistry of deep-sea sediments recovered during Ocean Drilling Program Leg 177 in the southeastern Atlantic sector of the Southern Ocean reveal several important aspects of paleocirculation and terrigenous provenance. The sites studied span 43°-53° S and represent different oceanographic settings relative to regional hydrography and sediment type. Bulk sediment geochemistry indicates that terrigenous provenance varied over the past 600 k.y. Site 1089, the northernmost site, exhibits clear glacial-interglacial variability in provenance, while provenance appears to vary regardless of climate state at the more southerly sites (Site 1093 and 1094). Nd and Sr isotopes and Sm/Nd ratios of the terrigenous fraction indicate that study sites have geochemically distinguishable provenance. Nd and Sr isotopes further suggest that Sites 1089 and 1094 both contain detrital components that originated in South America over the past 30 k.y.; however, Site 1089 is also influenced by southern African sources and the strength of the Agulhas Current. The εNd data support a more hemipelagic source for the terrigenous material rather than an eolian source based on comparisons with Antarctic ice core data and known sea-ice extent. © 2006 Geological Society of America.
Keywords: GLACIAL; INTERGLACIAL; PROVENANCE; SOUTHERN OCEAN; TERRIGENOUS MATERIALS